Position Tracking for Static Target using Burst Signals with Time Difference of Arrival Method - Romi Wiryadinata; Alia Shaliha Amany; Imamul Muttakin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Time difference of arrival (TDOA) is one of transmitter tracking method to find location or position based on the difference of arrival signals from transmitter to receiver in time domain. This work aims to find the position of a transmitter using TDOA method. Operating frequency used is amateur radio 144.100 MHz for sending and receiving burst signal. Time difference is calculated by using cross correlation function. Output parameters are distance and coordinate of Tx toward Rx. The transmitter position is calculated by hyperbolic and trigonometry equations, giving distance error of 30.49%. Further improvement would require two or more tracking position methods in order to obtain more accurate value.